Pengaruh Infrastruktur Terhadap Kesejahteraan Masyarakat Di Wilayah Tertinggal, Terluar Dan Terdepan - Raka Rifaldi Racsyah; Dedy Yuliawan; Muhammad Husaini (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the effect of infrastructure on community welfare in the underdeveloped, frontier, and outermost (3T) regions of Eastern Indonesia, measured by Gross Regional Domestic Product (GRDP) per capita. The independent variables include electricity distribution, access to proper sanitation, road conditions, and the number of health facilities, using cross-section data from 51 districts in 7 provinces in 2023 obtained from the Central Statistics Agency (BPS), and analyzed with multiple linear regression using the Ordinary Least Square (OLS) method. The results show that road conditions, access to proper sanitation, and the number of health facilities have a positive and significant effect on GRDP per capita, while electricity distribution has a negative but insignificant effect; simultaneously, all variables significantly affect GRDP per capita. These findings emphasize that improving basic infrastructure is a key factor in driving economic growth and community welfare in 3T regions, and can serve as a basis for more inclusive and equitable development.